2010
DOI: 10.2176/nmc.50.236
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Transformation 20 Years After Partial Removal of Intracranial Epidermoid Cyst -Case Report-

Abstract: A 74-year-old woman presented with malignant progression of remnant epidermoid cyst manifesting as sudden onset of right ptosis and double vision. She had right oculomotor nerve paresis. She had a history of surgery for right cerebellopontine angle epidermoid cyst 20 years previously. T 1 -weighted magnetic resonance (MR) imaging demonstrated a hypointense mass lesion in the right cerebellopontine angle and basal cistern, and an isointense mass in the right paraclinoid region which was strongly enhanced. Diffu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 17 publications
1
52
0
Order By: Relevance
“…Malignant transformation of an epidermoid cyst is a well-documented but rare occurrence (2,6). The rapid progression of signs and symptoms is the most important clinical indication of malignant transformation of epidermoid cysts (8). The exact mechanism of malignant changes of epidermoid cysts remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Malignant transformation of an epidermoid cyst is a well-documented but rare occurrence (2,6). The rapid progression of signs and symptoms is the most important clinical indication of malignant transformation of epidermoid cysts (8). The exact mechanism of malignant changes of epidermoid cysts remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…As desquamation occurs, the cystic cavity fills with epithelial cells consisting predominantly of keratin in concentric layers, water and cholesterol from cell membrane degradation, giving the tumor its pearly appearance. 1,3,4,6,14,15 Calcification is believed to be present in 10% of intracranial epidermoids. 9,16 Grossly, the lesion is well-defined with either a smooth or lobulated, cauliflower-like surface, contained within a pearly colored capsule.…”
Section: Pathology and Histologymentioning
confidence: 99%
“…[1][2][3] They have also been referred to as epidermoids, epidermoid tumors, and ''congenital cholesteatomas,'' which should be distinguished from ''acquired cholesteatomas'' caused by chronic middle ear infections. 4,5…”
Section: Introductionmentioning
confidence: 99%
“…However, this population presumably included survival data from two patients treated with stereotactic radiosurgery, one of which also received chemotherapy; these confounding factors may have biased their results. Similarly, Nakao et al 20 reported patients in which their malignant epidermoid developed from benign remnant tissue long after initial surgery. In these four patients, treatment with postoperative radiotherapy extended survival to a mean follow-up of 31.5 months.…”
Section: Discussionmentioning
confidence: 92%